THE INFLUENCE OF MATERNAL NUTRITION DURING PREGNANCY ON CHILDHOOD OBESITY RISK - Julia Kamińska; Karolina Strzelecka; Ewa Jagodzińska; Zuzanna Jabłońska; Maja Jabłońska; Antoni Plasota; Joanna Zygadło; Wiktor Milewczyk; Wojciech Michalski; Mikołaj Olczak (International Journal of Innovative Technologies in Social Science, 2026)
Childhood obesity is an urgent global concern. Growing evidence suggests its roots often extend back to prenatal development. This review examines how maternal nutrition influences the risk of childhood obesity through fetal metabolic programming. A literature search (October–December 2025) was conducted using PubMed, Scopus, Web of Science, and Google Scholar. It identified peer-reviewed studies on maternal diet, metabolic pathways, and long-term offspring health. Maternal macronutrient imbalances, such as excessive energy intake, high glycemic load, high saturated fat intake, or inadequate protein, were associated with altered fetal hormonal regulation. They also led to changes in placental nutrient transfer and epigenetic modifications. These changes affect insulin sensitivity and adipose tissue development. Micronutrient deficiencies, especially vitamin D, folate, and B12, were linked to disrupted metabolic signaling. They were also linked to adverse growth patterns. Maternal conditions, including obesity and gestational diabetes, further increased fetal susceptibility to obesity. This occurs by promoting hyperinsulinemia and adiposity before birth. Other factors, such as maternal genetics, gut microbiota, and early postnatal feeding, also interact with prenatal nutrition to shape long-term outcomes. The evidence highlights pregnancy as a key window for prevention. More longitudinal studies and biomarker-based dietary assessment are needed to support tailored nutritional guidance.